2023
DOI: 10.3389/fnhum.2023.1144860
|View full text |Cite
|
Sign up to set email alerts
|

Generalizability of muscle synergies in isometric force generation versus point-to-point reaching in the human upper extremity workspace

Katherine Pham,
Manuel Portilla-Jiménez,
Jinsook Roh

Abstract: Isometric force generation and kinematic reaching in the upper extremity has been found to be represented by a limited number of muscle synergies, even across task-specific variations. However, the extent of the generalizability of muscle synergies between these two motor tasks within the arm workspace remains unknown. In this study, we recorded electromyographic (EMG) signals from 13 different arm, shoulder, and back muscles of ten healthy individuals while they performed isometric and kinematic center-out ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Similar to the good-enough control strategy (Loeb, 2021 ), generalizable muscle synergies can be utilized across various motor contexts with reasonably good performance. While there is room for debate on such synergies, it can be potentially relevant to the shared muscle synergies observed in various static (Ting and Macpherson, 2005 ; Torres-Oviedo et al, 2006 ; Roh et al, 2012 ; Leonardis et al, 2020 ; Pham et al, 2023 ) and dynamic motor tasks or contexts (d'Avella and Bizzi, 2005 ; Chvatal and Ting, 2013 ; Barroso et al, 2014 ). Interestingly, in the lower limb static task of the cat (Torres-Oviedo et al, 2006 ), the experimental study reported that the rotation of the force direction exerted by shared muscle synergies is similar to limb axis rotation angles (McKay and Ting, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the good-enough control strategy (Loeb, 2021 ), generalizable muscle synergies can be utilized across various motor contexts with reasonably good performance. While there is room for debate on such synergies, it can be potentially relevant to the shared muscle synergies observed in various static (Ting and Macpherson, 2005 ; Torres-Oviedo et al, 2006 ; Roh et al, 2012 ; Leonardis et al, 2020 ; Pham et al, 2023 ) and dynamic motor tasks or contexts (d'Avella and Bizzi, 2005 ; Chvatal and Ting, 2013 ; Barroso et al, 2014 ). Interestingly, in the lower limb static task of the cat (Torres-Oviedo et al, 2006 ), the experimental study reported that the rotation of the force direction exerted by shared muscle synergies is similar to limb axis rotation angles (McKay and Ting, 2008 ).…”
Section: Discussionmentioning
confidence: 99%